Correlation between inner retinal layer thickness and cognitive function in HIV: new insights from an exploratory study. (17th July 2018) - Invernizzi, Alessandro; Acquistapace, Alessandra; Bochicchio, Sara; Resnati, Chiara; Rusconi, Stefano; Ferrari, Marta; Leta, Valentina; Pomati, Simone; Klistorner, Alexander; Mccluskey, Peter; Staurenghi, Giovanni; Riva, Agostino
Abstract : Objective: To compare retinal layer thickness in HIV-infected subjects with (CI-HIV) and without (NCI-HIV) cognitive impairment, with a control population and to correlate this with the cognitive status of the patient and other clinical parameters. Design: Single-center cross-sectional study. Methods: Participants with controlled HIV infection aged between 40 and 70 years and sex-matched and age-matched controls were enrolled. Retinal nerve fiber layer (RNFL), ganglion cell layer (GCL) and inner plexiform layer (IPL) thickness were assessed using optical coherence tomography. These measurements in HIV patients were compared with those in controls. Age-related and sex-related changes were compared in both groups. Other variables studied in HIV patients included: duration of HIV infection, CD4 + cell count nadir, antiretroviral therapy regimen and cognitive status using the Montreal Cognitive Assessment (MoCA) test. Results: Sixty-nine individuals, 34 with and 35 without cognitive impairment, and 70 controls were enrolled. GCL was significantly thinner in CI-HIV patients compared with NCI-HIV patients and controls ( P  = 0.01 and P  = 0.02, respectively). GCL and IPL thickness significantly decreased with age in patients with HIV ( P  = 0.0003, P  = 0.02, respectively, for the entire cohort). This change was not seen in controls. MoCA test score significantly decreased with age in HIV patients and controls. GCL thickness positively correlated with cognitive function across the entire HIV cohort ( P  = 0.02). Conclusion: GCL was thinner in HIV patients with cognitive impairment. GCL thickness correlated positively with cognitive function and negatively with age in HIV patients. GCL thickness may reflect accelerated cognitive aging in HIV.